ANALISIS KESULITAN SISWA SMP KELAS VII DALAM MEMAHAMI MATERI SEGIEMPAT DAN SEGITIGA DALAM PEMBELAJARAN DARING - Isna Sani Hidayah; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Mathematics has an important role to play in life. But the reality in the field shows that many students still have difficulty in understanding math lessons, including geometry. The evidence in the field shows that the results of learning geometry are still low. The difficulty in understanding this geometry material has an impact on other materials related to the geometry material itself. Students will have difficulty in associating material with each other. This study aims to analyze the causes of students' difficulty in understanding Quadrilateral and Triangular materials in online learning. The research method used is qualitative method with case study type. The research subjects were taken as many as 9 students from grade VII E MTs Negeri 3 Purwakarta. The results showed that there are still many students who have difficulty in triangular and quadrilateral materials in grade VII MTs Negeri 3 Purwakarta caused by several different factors.